Unlocking Value : Alternative Fuels for Egypt’s Cement Industry - International Finance Corporation (World Bank, Cairo, 2016)
The report identifies viable and low-carbon energy sources that would help cement producers satisfy their growing energy demand. For the first time, mapped, quantified, and analyzedco-processing in Egypt. It also identified the current and future appetite for alternative fuels, highlighted impediments to market growth, and recommended potential solutions throughout the supply chain. This study makes that point clear, and encourages producers, officials, and other stakeholders to find greener ways to help Egypt’s cement industry grow. The successful use of alternative fuels for the cement industry brings with it potentially significant public and private benefits. The use of Alternative Fuels and Raw Materials (AFR) can reduce landfilling, lower carbon emissions by substituting the use of coal, reduce public costs for waste management, and potentially transform waste from a public nuisance into a privatizedand lucrative solution. The benefits make the investment more than worth the effort.Alternative Fuels and Raw Materials (AFR) are any non-fossil based fuels that can replace part of the raw material needed for the production of cement, whether it is used for thermal energy or material recovery. These alternative fuels are derived from waste material, which is plentiful in Egypt. The main objective of this study will be to examine in detail the financial viability, economic competitiveness, technical feasibility and other benefits of AFR for the cement industry. This report will consider four types of AFR waste streams: a) refuse derived fuel (RDF) from municipal solid waste, b) dried sewage sludge (DSS) from wastewater treatment plants, c) agricultural waste, and d)tire derived fuel (TDF) from scrap tires. These waste streams have been selected since they meet three essential criteria defined after extensive consultation with relevant stakeholders. Those are: 1) suitability for use by the Egyptian cement industry; 2) abundance, relative availability of data, and proximity to cement producers; and 3) current mismanagement of associated waste streams, leading to negative environmental and health impacts. Conclusions can be drawn largely on the price differential between AFR and conventional fuel, which may depend in large part onEgypt’s energy and waste management policies. Expanded use of alternative fuels will be further stimulated by the introduction of an economic framework around waste disposal and recycling.A more detailed analysis of the existing regulatory framework, future policies needed and international best practices will also be elaborated upon. Based on the assessment of the energy situation in Egypt, the cement industry’s thermal energy needs, and the current use of AFR, a realistic energy mix scenario will be developed. This will also involve a comparison of the energetic (calorific) value of the various energy sources, potential volumes available, and the cost structure. This study aims to provide a reference for the cement industry, waste processing companies, and Egyptian authorities, helping them to understand and identify responsible and sustainable approaches tothe selection and use of AFR in the cement industry in a transparent and sustainable manner.